Chirality and frequency measurement of longitudinal rolling of human sperm using optical trap - Zhong, Zhensheng; Zhang, Can; Liu, Rui; He, Jun; Yang, Han; Cheng, Zijie; Wang, Tao; Shao, Meng; Fang, Shu; Zhang, Shengzhao; Shi, Hui; Xue, Rufeng; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Motility is one of the most critical features to evaluate sperm quality. As longitudinal rolling of human sperm has long been ignored until recently, its detailed dynamics and cellular biological mechanisms are still largely unknown. Here we report an optical-tweezers-based method to evaluate the chirality and frequency of sperm rotation. According to the intensity distribution patterns of off-focus micron-size particles, we established a method to judge the orientation of the sperm head along the optical axis in the optical trap. Together with the rotation direction of the projection of the sperm head, the chirality of longitudinal rolling of sperm can be measured without the application of three-dimensional tracking techniques or complex optical design. By video tracking optically trapped sperm cells from different patients, both rolling chirality and rolling frequency were analyzed. In this study, all the vertically trapped human sperm cells adopt a right-hand longitudinal rolling. The orientation and rolling behavior but not the rolling chirality of sperm in the optical trap are affected by the trap height. The rotation analysis method developed in this study may have clinical potential for sperm quality evaluation.